2011
DOI: 10.1590/s1809-29502011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Pontos marcados na superfície da pele representam os processos espinhosos quando a postura é modificada?

Abstract: O objetivo do estudo foi verificar radiograficamente se a posição dos marcadores de superfície, identificados por palpação em ortostase, é alterada com a modificação da postura para o decúbito lateral. Dez indivíduos foram: palpados e marcados com adesivos de superfície, os processos espinhosos das vértebras C7, T2, T4, T6, T8, T10, T12, L2, L4 e S2; submetidos a um exame radiológico da coluna vertebral na posição ortostática e em decúbito lateral direito para verificar se o marcador de superfície colocado sob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…According to Saad et al [28] marking is subject to the interference of soft tissue, and significant alterations might occur in the correspondence of the marker on the skin in relation to the anatomic segment. Furlanetto et al [29] and Saad et al [28] also suggested that the marking of points might be compromised when palpation occurs in a different position from that to be evaluated, and hence in order to avoid these errors, marking should be always carried out by the same evaluator and in the position to be evaluated. In this study, the elderly individuals were marked in the same position as that in which they would be evaluated, and all by the same evaluator, who has about 15 years of experience in posture evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Saad et al [28] marking is subject to the interference of soft tissue, and significant alterations might occur in the correspondence of the marker on the skin in relation to the anatomic segment. Furlanetto et al [29] and Saad et al [28] also suggested that the marking of points might be compromised when palpation occurs in a different position from that to be evaluated, and hence in order to avoid these errors, marking should be always carried out by the same evaluator and in the position to be evaluated. In this study, the elderly individuals were marked in the same position as that in which they would be evaluated, and all by the same evaluator, who has about 15 years of experience in posture evaluation.…”
Section: Discussionmentioning
confidence: 99%